Memories of post-imperial nations: the aftermath of decolonization, 1945-2013 - Rothermund, Dietmar (Cambridge University Press, 2015)
Memories of Post-Imperial Nations presents the first transnational comparison of Great Britain, the Netherlands, Belgium, France, Portugal, Italy and Japan, all of whom lost or 'decolonized' their overseas empires after 1945. Since the empires of the world crumbled, the post-imperial nations have been struggling to come to terms with the present, and as recall sets in 'wars of memory' have arisen, leading to a process of collective 'editing'. As these nations rebuild themselves they shed old characteristics and acquire new ones, looking at new orientations. This book brings together varying perspectives with historians and political scientists of these nations attempting to bind memory and its experience of different post-imperial nations.
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Europe -- Colonies -- Historiography; Japan -- Colonies -- Historiography; Aufsatzsammlung; Geschichte 1945-2013; Kollektives Gedächtnis; Geschichtsschreibung; Kolonialmacht; Entkolonialisierung